INSTAGRAM APPLICATION: AN ACTIVE TOOL IN CULTIVATING READING BEHAVIOUR - Alzairin Morshidi; Mohamed Amin Embi; Harwati Hashim (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
The fourth wave of the industrial revolution has brought tremendous changes to our education system. The use of technology in teaching and learning give a great effect on not only pupils but teachers as well. Technologies also give an opportunity for students and teachers to learn from a broader perspective of learning other skills. As the education system is transforming to a better version, it somehow requires the teachers to be fully equipped with the advancement of technology to develop pupils’ potential qualities hence there is a growing need for ESL teachers to find a more interactive and fun approach. Recently, technology development has changed pupils’ demand in selecting their reading materials. Most of pupils’ these days feel that reading is not an attractive activity as they will easier feel bored and short attention span. Unattractive reading materials might give opposite results in enhancing pupils’ behaviour in reading. Reading skill is one of the vital elements in helping pupils to enhance their English language proficiency. Therefore, the study will investigate the use of the Instagram application in cultivating reading behaviour among pupils. The study was conducted with 30 pupils in urban area school in Melaka. The data was collected via observation, interview and questionnaire to measure the outcome. The finding showed the positive impact in cultivating the reading behaviour among pupils through Instagram. This research is beneficial to the teaching community as it provides an innovative approach teaching in ESL classroom. Thus, it is hoped that Instagram application able to improve pupils’ behaviour in reading